2022
DOI: 10.1002/brb3.2493
|View full text |Cite
|
Sign up to set email alerts
|

Is psychological distress associated with carpal tunnel syndrome symptoms and nerve conduction study findings? A case–control study from Syria

Abstract: Background:Carpal tunnel syndrome (CTS) is a common entrapment neuropathy of the median nerve at the wrist which causes severe symptoms. However, psychological aspects can affect how patient perceive this pain and can cause similar pain in some instances. This study aims to determine the association between symptoms severity, functional status, and nerve conduction studies (NCS) of adult patients with carpal tunnel syndrome (CTS) and their anger, anxiety, and depression status. Methods:This case-control study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Our finding concerning this relationship is the case in the studies of Núñez-Cortés et al (2023); Moro-López-Menchero et al (2023); Daliri et al (2022); Sun et al (2019); Alsharif et al (2022); and Kurtul & Mazican (2023) [ 4 , 6 , 10 , 12 , 18 , 56 ]. There is a consensus in these studies that adaptive coping of patients with disease and the resultant stress could decrease pain perception among CTS patients, which further increases the pain threshold and decreases pain intensity among patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our finding concerning this relationship is the case in the studies of Núñez-Cortés et al (2023); Moro-López-Menchero et al (2023); Daliri et al (2022); Sun et al (2019); Alsharif et al (2022); and Kurtul & Mazican (2023) [ 4 , 6 , 10 , 12 , 18 , 56 ]. There is a consensus in these studies that adaptive coping of patients with disease and the resultant stress could decrease pain perception among CTS patients, which further increases the pain threshold and decreases pain intensity among patients.…”
Section: Discussionsupporting
confidence: 72%
“…Adaptive coping strategies are effective in reducing stress and improving psychological and physical well-being. These strategies include seeking support from friends, family, or support groups; alternating job functions; avoiding repetitive motions; scheduled rest and breaks; heat and cold compresses; problem-solving techniques such as ergonomic adjustments or wrist splints; relaxation techniques such as deep breathing or mindfulness; and maintaining a positive mindset [ 5 , 12 ]. Adaptive coping strategies help manage and alleviate CTS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that psychological status and illness behavior can play a role in the severity of perceived preoperative CTS symptoms and diminished postoperative patient satisfaction following CTR. 30 , 38 , 39 , 40 , 41 A significant portion of our patients who underwent revision CTR carried a psychiatric diagnosis (43.5%). Although it is possible that patients with a psychiatric history were less likely to be satisfied with CTR and more likely to catastrophize recurrent or persistent symptoms, no definitive conclusions can be made from this retrospective study.…”
Section: Discussionmentioning
confidence: 93%
“…We found a limited relationship between items related to paraesthesia intensity and magnitude of capability and objective pathophysiology, and no relationship with pain intensity. This suggests that BCTQ scores might largely be driven by other effects known to account for variation in symptom intensity and magnitude of capability, such as non-specific issues (placebo effect, regression to the mean), mental health (unhelpful thoughts and distress) and social health (insecurity in job, role, housing, food, finances) (Alsharif et al, 2022;Fernandez-de-las-Penas et al, 2015;Nunez et al, 2010;Shin et al, 2018;Sun et al, 2019). The findings of this study should be interpreted in light of some limitations.…”
Section: Discussionmentioning
confidence: 99%